A first principles study on the ground state properties of three ferromagnetic skutterudites NdB4As12 (B = Fe, Ru, Os). (13th September 2019) - Chaki, T; Barman, N; Shankar, A; Mandal, P K
Abstract: Structural, electronic, magnetic and optical properties of three neodymium filled skutterudites NdB4 As12 (where B = Fe, Ru, Os) have been studied by using FP-LAPW method. PBE-GGA has been used for the exchange–correlation potential. Osmium based skutterudite is found to have maximum stiffness to external pressure. All three compounds exhibit similar band structures. Concentration of bands near the Fermi level, presence of pseudo band gaps above the Fermi level and crossing the Fermi level of bands originating from the conduction region suggest the metallic nature of the materials. The compounds are also expected to be suitable for thermoelectric application. Splitting of f states of Nd atoms, observed in spin dependent DOS studies, signifies ferromagnetic nature of the Fe, Ru, Os based compounds with effective magnetic moment of 2.149 μ B, 3.573 μ B and 3.379 μ B, respectively. Complex dielectric function, refractive index and optical conductivity have also been calculated in the photon energy range (0–14 eV).